PENYELESAIAN SENGKETA TANAH ANTARA PEMERINTAH REPUBLIK INDONESIA C.Q TENTARA NASIONAL INDONESIA ANGKATAN UDARA DENGAN MASYARAKAT ADAT DI WILAYAH KABUPATEN MOROTAI MALUKU UTARA - Windardi, Ichsan Ahmad; Sudarto, Sudarto; Gultom, Potler (LITERATUS, 2024)
Land is an asset that has an important meaning for every individual in society. Apart from having economic value that can be reserved as a source of human life support in the future, land also contains spiritual aspects in the environment and its survival. Land is a place of settlement, a place to carry out human activities, even after death it still needs land. Land in the plains of Indonesia is a source of livelihood for the community and income for those who earn income from agriculture. In the political aspect, land is the place, boundary, and location of the jurisdiction of the Indonesian population, while from the social aspect, land is a space for good relations between fellow Indonesians. The holder of the right to the surface of the earth (Landowner) is given the right to do something about the land that legally belongs to him. The term something that can, must or is prohibited to be done is the content of the right of the ruler. This is the criterion or benchmark for distinguishing between land tenure rights which are then regulated in land law or land regulations. The existing land regulations in Indonesia are regulated in Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles (hereinafter shortened to (UUPA)), providing affirmation of arrangements related to the surface of the earth in a juridical sense called land tenure rights. Land tenure includes the relationship between individuals, (individuals) legal entities, or communities as a collectivity with land that is haki resulting in the birth of rights and obligations. Agrarian land conflicts still often occur in various regions in Indonesia, especially on the issue of natural resource management with the assumption of increasing economic growth. Land issues between land rights holders dealing with the ruling government tend to change as a result of the ever-changing land configuration, resulting in a clash of interests that continues to grow so that a dispute resolution approach is needed that can provide justice and legal certainty for the community. This also happened in the eastern border area of Indonesia, namely Morotai Island Regency, North Maluku Province.